La crítica de Nietzsche al estado moderno - Vita, Leticia (2009)
This article presents a systematization of Friedrich Nietzsche's work, oriented towards his criticism to the State, Religion and Law. It may be divided into two sections. The first one is devoted to a brief examination of his criticism\nto Hegelian thought and Max Strimer's influence in his work. The second one,\nto explaining Nietzsche's criticism to religion and the creation of God by mankind\nas a justification for power, State and its legal structure. Finally, the notion of Nietzsche as a Nazi, arising out of the censorship applied by his sister to his writings, is rebutted and the thinker's anti-German ideas and his hatred towards Nazism is put across. The conclusion of the article shows Nietzsche as an antiState\nthinker, firmly opposed to political domination